A Hybrid Line Search Technique with Modified Goldstein and Wolfe Conditions - Sawsan S. Ismael Department of Math (College of Education for Pure Sciences, 2013)
ABSTRACT Modified Goldstein or Wolfe conditions can be imposed on a hybrid line search to ensure the convergence property of an iterative nonlinear optimization algorithm to a stationary point. Modifying these conditions can make it significantly easier to find an acceptable step size. Our numerical results indicate that the new proposed line search beats the standard one ,for a selected nine test functions